The Protective Effects Of Beta Glucan Against Experimental Renal Ischemia Reperfusion Injury - Ferhat Şirinyıldız; Ayşegül Mavi Bulut; Gökhan Cesur; Cenk Orak (Acta Medica Alanya)
Aim: This study aims to investigate the possible protective effects of beta-glucan against oxidative stress caused by ischemia and reperfusion injury in kidney tissue.Methods: In the study, 30 male Wistar albino rats weighing 300-350g were used (n=10). Rats were randomly grouped into three groups of Sham control, ischemia reperfusion group (IR), ischemia reperfusion + beta glucan group (IR + BG). Sham group had left nephrectomy, the right kidney taken for histopathologic and biochemical examination. After left nephrectomy in IR group, ischemia procedure was applied for 45 minutes via nontraumatic microvascular clamp, then reperfusion was applied for 60 minutes in the right kidney. In the IR+BG group, rats were administered 100 mg/kg beta glucan via gastric gavage for 10 days. Reperfusion was applied for 60 minutes after 45 minutes of ischemia to the right kidney under anesthesia.Results: As a result of biochemical examination MDA values showed a significant increase in IR group compared to Sham group (p<0,05). In IR+BG group, there was a significant decrease compared to IR group (p<0,05). Tissue MPO values in IR group showed a significant increase compared to Sham group, whereas in the IR+BG group there was not a significant decrease. Also, there was not a significant difference in tissue catalase levels. Tissue GSH values showed a significant decrease in IR group compared to Sham group (p<0,05). In the IR+BG group a significant increase was found compared to IR group (p<0,05). Less damage has been revealed in the IR+BG group compared to IR group in histopathologic examination.Conclusion: All these data show that beta glucan may have an antioxidant effect on renal ischemia reperfusion injury.